Bio convection heat transfer in Sisko nanofluid past a stretching cylinder with Soret and Dufour effects - Rafique, Khuram; Elkahlout, Gamal; Rehman, Ayesha; Kanwal, Shamaila (Edelweiss Applied Science and Technology, 2024)
The present flow model provides useful information for the production of nano-biomaterials, medical treatment, materials science current research model has been utilized. The unique thermal mechanisms of nanoparticles have garnered significant attention from researchers in recent years. These versatile materials have numerous applications in various fields, including cooling and heating control processes, solar systems, energy production, nanoelectronics, hybrid-powered motors, cancer treatments, and renewable energy systems. Furthermore, the bioconvection of nanofluids has exciting implications for bioengineering and biotechnology, with potential uses in biofuels, biosensors, and enzymes. The aim of this study is to investigate the flow behaviour of bioconvection Sisko nanofluid flow through a stretching cylindrical surface. Further, the analysis has been modified by including the effects of Soret and Dufour. The highly nonlinear and coupled differential equations were numerically solved using a BVP4c solver to simulate the problem. The effects of different flow parameters on velocity, temperature, and concentration distributions are examined and illustrated through graphical results. It is clearly observed from the results that Soret impacts increases the concentration distribution. Moreover, Dufour impacts increment increases the temperature of the flow.